2-ARACHIDONOYLGLYCEROL STIMULATES AP-1-DEPENDENT TRANSCRIPTIONAL ACTIVITY AND ENHANCES EGF-INDUCED CELL TRANSFORMATION IN JB6 P(+) CELLS - Zhao, Qing (2005)
2-arachidonoylglycerol (2-AG) is the most abundant endocannabinoid and it plays a critical role in cannabinoid receptor-mediated cell signaling. Although 2-AG was shown to induce ERK activation via the cannabinoid receptor 1 (CB1), only a nonspecific CB receptor agonist and antagonist was used in those studies. Whether cannabinoid receptor 2 (CB2) is involved in 2-AG-induced ERK activation is still unclear. Moreover, whether 2-AG is involved in mediation of AP-1 activity and cell transformation is also not known. In the present study, we show that 2-AG stimulates AP-1-dependent transcriptional activity and enhances EGF-induced cell transformation in mouse epidermal JB6 P(+) Cl41 cells. Using JB6 P(+) C141 cells, stably transfected with an AP-1 luciferase reporter, we found that 10 μM 2-AG induced up to a 3-fold stimulation of AP-1 transcriptional activity. The AP-1 stimulation appeared to be mediated by ERK, but not JNK or p38 kinase. PD98059, a specific inhibitor of MEK1, almost completely blocked 2-AG-induced ERKs phosphorylation and AP-1 activation. Using CB1/2(−/−) murine embryonic fibroblasts (MEFs), we present the first direct evidence that both of cannabinoid receptors 1 and 2 (CB1/2) are involved in 2-AG-induced ERK activation. 2-AG could not stimulate ERK phosphorylation or Fyn kinase activity in dominant negative Fyn. In addition, the Fyn inhibitor, PP2, blocked 2-AG-induced Fyn kinase activity and ERKs phosphorylation and activity. siRNA Fyn also suppressed 2-AG-induced ERKs phosphorylation. Interestingly, 2-AG enhanced EGF-induced AP-1 DNA binding and cell transformation. Taken together, our data provide direct evidence suggesting that 2-AG may have a novel role in cell transformation and carcinogenesis in a signaling pathway involving CB1/2 and activation of Fyn, ERKs and AP-1.